Formation and evolution of mountainous aeolian sediments in the northern Tibet Plateau and their links to the Asian winter monsoon and westerlies since the Last Glacial Maximum. (February 2022) - Peng, Simin; li, Yu; Liu, Hebin; Han, Qin; Zhang, Xinzhong; Feng, Zhuowen; Chen, Dawei; Ye, Wangting; Zhang, Yuxin
The production, transport, and deposition of dust has profound impacts and feedbacks on the regional and global environments. In parallel, the Tibet Plateau (TP) plays an important role in East Asian and global climate systems. Previous studies have shown that the dust can reach the plateau by long-distance transport from the westerlies and by short-distance transport from regional weathering. Here we present three new datasets in the Qilian Mountains of the northern TP, including two mountainous aeolian sedimentary sequences and a surface sample dataset. Proxies include grain size, magnetic susceptibility, mineral composition, total organic carbon, and total nitrogen. Data from surface samples indicate spatial gradient effects in altitude (from low to high) and latitude (from north to south), suggesting dust transport from the Gobi Desert to the plateau. The synthetic analysis of two aeolian sedimentary sequences and paleoclimate simulation data reveals that the northern TP can be a dust transport channel controlled mainly by the Asian winter monsoon and less influenced by the westerlies.